2013
DOI: 10.1016/j.jbiomech.2012.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Advances in assessment of bone porosity, permeability and interstitial fluid flow

Abstract: This contribution reviews recent research performed to assess the porosity and permeability of bone tissue with the objective of understanding interstitial fluid movement. Bone tissue mechanotransduction is considered to occur due to the passage of interstitial pore fluid adjacent to dendritic cell structures in the lacunar-canalicular porosity. The movement of interstitial fluid is also necessary for the nutrition of osteocytes. This review will focus on four topics related to improved assessment of bone inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
103
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(113 citation statements)
references
References 103 publications
9
103
1
Order By: Relevance
“…This porosity contains the osteocytes' stellar network of bone (typical pore size of 100 nm) and the smallest porosity level in bone corresponds to the spaces inside the collagen-apatite structure (typical pore size of 5 nm). At this nanoconfined environment, water strongly interacts with the ionic crystal [25,26] and plays a key role in structuring the apatite mineral [27,28] and during mineralization [29] by acting as a prominent charge carrier, maintaining the pH of the medium, and transporting ions [26].…”
Section: Introductionmentioning
confidence: 99%
“…This porosity contains the osteocytes' stellar network of bone (typical pore size of 100 nm) and the smallest porosity level in bone corresponds to the spaces inside the collagen-apatite structure (typical pore size of 5 nm). At this nanoconfined environment, water strongly interacts with the ionic crystal [25,26] and plays a key role in structuring the apatite mineral [27,28] and during mineralization [29] by acting as a prominent charge carrier, maintaining the pH of the medium, and transporting ions [26].…”
Section: Introductionmentioning
confidence: 99%
“…Although the LCN is raising increasing interest, it is a structure difficult to assess since it is deeply embedded in calcified bone matrix and it is composed of a huge number of nanometric structures. Lacunae are flat ellipsoidal voids housing the osteocyte bodies and with a density between 26000 to 90000/mm 3 (Cardoso et al, 2013). Canaliculi are narrow tunnels, enclosing the cell processes of the osteocytes with a reported diameter around 100-700 nm (You et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The correct order of magnitude of bone permeability is still a matter of debate (Cardoso et al, 2013). Previous computational studies (Pereira and Shefelbine, 2014) showed that poroelastic models with bone permeability k = 10 −22 m 2 simulate relaxation times similar to in vivo measures in mice and consistent with recent experimental estimations (Benalla et al, 2014).…”
Section: Constitutive Assumptions For Permeability Of Bone and Membranessupporting
confidence: 67%